The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.4103/2230-9748.106980
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of laryngeal hyperfunction with flow phonation: A pilot study

Abstract: Context:While clinical successes and descriptions have been reported in a few texts, no data exist to define the utility of flow phonation to improve voice quality in patients with laryngeal hyperfunction. Aims: To provide pilot data regarding the utility of three exercises (gargling, cup bubble blowing, and stretch-and-flow) to improve phonatory airflow during voicing in patients with laryngeal hyperfunction. Settings and Design: Outpatient Voice and Swallowing Center in a University Medical Center. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 12 publications
1
8
0
1
Order By: Relevance
“…Our sample size was particularly small. We determined sample size on the basis of statistical results from pilot data (McCullough et al, 2012), but those data were focused on the exercises themselves and not the use of telehealth technology. As stated, larger numbers guided by detailed power analyses are needed to more critically examine different types of MTD and changes in Rlaw in relation to phonatory airflow and tease out the effects of initial severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our sample size was particularly small. We determined sample size on the basis of statistical results from pilot data (McCullough et al, 2012), but those data were focused on the exercises themselves and not the use of telehealth technology. As stated, larger numbers guided by detailed power analyses are needed to more critically examine different types of MTD and changes in Rlaw in relation to phonatory airflow and tease out the effects of initial severity.…”
Section: Discussionmentioning
confidence: 99%
“…Variants of these exercises have been used with reported clinical success (Gartner-Schmidt, 2010). McCullough et al (2012) recently provided the first data-based study of this method's utility for improving airflow and decreasing symptoms of vocal hyperfunction. The authors reported data from six participants who were treated for primary MTD using flow phonation exercises for a 6-week period.…”
Section: Mtdmentioning
confidence: 99%
“…These studies provide a reasonable justification for the call for improved scientific evaluation of intervention effectiveness. However, to date, only two case series (Robey Phase 2) have examined the effects of flow phonation in a clinical population …”
Section: Evaluation Of the Evidencementioning
confidence: 99%
“…However, to date, only two case series (Robey Phase 2) have examined the effects of flow phonation in a clinical population. 35,36 The need for careful and detailed documentation of therapy content has also received some attention in recent literature. Some key studies provide a detailed description of therapy content to allow for replication (e.g.…”
Section: Phasementioning
confidence: 99%
“…Stretch‐and‐flow (S n F) is a voice therapy program that targets attainment of a physiological balance between the vocal subsystems in patients with hyperfunctional voice disorders. S n F was first described by Stone and Casteel in the early 1980s and has also been referred to as flow phonation by a number of authors and clinicians . The fundamental target in S n F is to initiate volitional control over the vocal subsystems using voiced and unvoiced airflow stimuli while maintaining a perception of minimal muscular effort during phonation .…”
Section: Introductionmentioning
confidence: 99%